Penerapan Model Pembelajaran POE (Predict-Observe-Explain) Terhadap Kemampuan Penalaran Matematis Siswa Sekolah Dasar - Arya Setya Nugroho; Ivanah Cahyani Mulyaningrum F (DIDAKTIKA, 2024)
This research was conducted at SD Muhammadiyah Gresik, Grade V, Academic Year 2023/2024. The purpose of this research is to determine the implementation of the POE (Predict-Observe-Explain) learning model's influence on the mathematical reasoning abilities of fifth-grade students in mathematics, specifically in comparing the characteristics of flat shapes in logical reasoning. This research is a quantitative study using the experimental method. The data collection techniques used are observation and questionnaires. The results of the hypothesis test calculation using the independent sample t-test obtained a significance value of 0.000 < 0.05, so H0 is rejected and H1 is accepted. Additionally, according to the hypothesis testing rule thitung ≥ ttabel, the result of 2.25 ≥ 1.99 indicates that H0 is rejected and H1 is accepted. Based on the results of the hypothesis test, it shows that the adaptive mathematical reasoning ability with the Predict Observe Explain learning model is higher compared to the adaptive mathematical reasoning ability of students taught with the conventional learning model. The results of the calculations can be concluded that there is a significant influence of the application of the POE (Predict-Observe-Explain) learning model on students' mathematical reasoning abilities.